The Newly Synthesized Pyrazole Derivative 5-(1-(3 Fluorophenyl)-1H-Pyrazol-4-yl)-2H-Tetrazole Reduces Blood Pressure of Spontaneously Hypertensive Rats via NO/cGMO Pathway - Trindade, Neidiane R.; Lopes, Paulo R.; Naves, Lara M.; Fajemiroye, James O.; Alves, Pedro H.; Amaral, Nathalia O.; Lião, Luciano M.; Rebelo, Ana C. S.; Castro, Carlos H.; Braga, Valdir A.; Menegatti, Ricardo; Pedrino, Gustavo R. (Frontiers in Physiology, 2018)
The search for new antihypertensive drugs has grown in recent years as a result of high rate of morbidity among hypertensive patients and several side effects that are associated with the first line medications. The current study sought to investigate the antihypertensive effect of a newly synthesized pyrazole derivative known as 5- (1- (3 Fluorophenyl)-1H-pyrazol-4-yl)-2H-tetrazole (LQFM-21). Spontaneously hypertensive rats (SHR) were used to evaluate the effect of LQFM-21 on mean arterial pressure (MAP), heart rate (HR), renal vascular conductance (RVC), arterial vascular conductance (AVC), baroreflex sensitivity index (BRS), and vascular reactivity. Acute intravenous (iv) administration of LQFM-21 (0.05, 0.1, 0.2, 0.4 mg ∙ kg-1) reduced MAP and HR, increased RVC and AVC. Chronic oral administration of LQFM-021 (15 mg ∙ kg-1) for 15 days reduced MAP without altering BRS. The blockade of muscarinic receptors and nitric oxide synthase by intravenous infusion of atropine and L-NAME, respectively, attenuated cardiovascular effects of LQFM-21. In addition, ex vivo experiments showed that LQFM-21 induced an endothelium-dependent relaxation in isolated aortic rings from SHR. This effect was blocked by guanylyl cyclase inhibitor (ODQ) and L-NAME. These findings suggest the involvement of muscarinic receptor and NO/cGMP pathway in the antihypertensive and vasodilator effects of LQFM-21.